Pengaruh Model PBL Terhadap Kemampuan Penyelesaian Soal Masalah Matematis Kelas IV SD - Aisyah; Renita Mila Rahmadhani; Lovika Ardana Riswari (Universitas Muhammadiyah Kuningan, 2024)
This research aims to explore the effect of implementing the PBL (Problem Based Learning) model on students' abilities in solving mathematical problems in class IV SD 2 Ploso. By focusing on providing material about flat shapes, this research measures differences in students' understanding abilities before and after learning using the t test on pretest and posttest scores. Before treatment, students took the pretest with an average score of 34, indicating a low initial level of understanding. After learning with PBL, the posttest results showed a significant increase with an average score reaching 63. Through the Paired t-test hypothesis test, the significance value (sig.) was 0.001, smaller than the probability of 0.05, indicating that there was a positive influence of the PBL model on students' ability to solve mathematical problems. Thus, it can be concluded that PBL is effective in improving the mathematical problem-solving ability of grade IV students.